EFFECTS OF N-3 POLYUNSATURATED FATTY ACIDS ON LEFT VENTRICULAR FUNCTION AND FUNCTIONAL CAPACITY IN PATIENTS WITH DILATED CARDIOMYOPATHY - S. Nodari; M. Triggiani; U. Campia; A. Manerba; G. Milesi; B. M. Cesana; M. Gheorghiade; L. Dei Cas (Рациональная фармакотерапия в кардиологии)
.